Inclusão como Possibilidade de Acesso e Permanência no IFSP: Campus Registro - Duarte, Amanda Machado dos Santos (Revista Letra Magna, 2022)
Esse artigo é um desdobramento de uma Tese de Doutorado que discutiu a permanência estudantil na Rede Federal de Educação Ciência e Tecnologia abrangendo as 5 regiões Brasil. Dada a extensão do material levantado, este recorte objetiva discorrer sobre as políticas de acesso e permanência institucional pautadas na ótica da inclusão e foca, mais especificamente, no Instituto Federal de São Paulo – IFSP Campus Registro. As análises e reflexões ocorrem por meio de dois instrumentos: as cartografias, elaboradas em 2019 por estudantes do campus e dados coletados por meio de entrevistas realizadas em 2021. As reflexões oriundas do contraste entre esses dados podem auxiliar na compreensão da conjuntura atual do país no contexto pandêmico bem como esclarecer de que modo as políticas de acesso e permanência mostram-se estratégias de colaboração essenciais para assegurar a inclusão educacional como um direito. Inclusion as a Possibility for Access and Permanence at IFSP – Campus Registro Abstract This article is an unfolding of a Doctoral Dissertation that discussed the permanence of students within the Federal Institute of Science, Technology and Education grid covering 5 regions of Brazil. Given the extent of the collected data, this article aims to discuss the policies of access and institutional permanence based on the perspective of inclusion and focuses, more specifically, on the Federal Institute of São Paulo – IFSP Campus Registro. The analyses and reflections occur through two instruments: the cartographies, elaborated in 2019 by campus students and data collected through interviews conducted in 2021. The reflections arising from the contrast between these data may help in understanding the current situation of the country in the pandemic context as well as to clarify how access and permanence policies work as essential collaborative strategies to ensure educational inclusion as a right. Keyword: inclusion, professional and technological education, high school, access and permanence